Penerapan Sistem Bank Soal dengan Metode Ishihara Berbasis IoT Pada Alat Tes Buta Warna - Windanita Tada Bale; Imam Tri Harsoyo (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2025)
Color blindness is a general term for a condition or condition in which the quality of color vision is impaired. People with color blindness have difficulty distinguishing certain shades of color. Color blindness is also called Color Vision Deficiency (CVD) taking into account the prevalence of color blindness in Indonesia of 0.7% which is a cause of disability. Therefore, it is necessary to develop an Internet of Things (IoT) based color blindness test tool with the application of a question bank system using the Ishihara method which can help users check for color perception disorders which can be implemented by checking color blindness early on. In designing this IoT-based color blindness test tool, measurements were taken on 30 respondents to check the accuracy of the tool that has been designed. This color blindness test tool has an accuracy of 97%. This color blindness test tool functions to help users more easily carry out color blindness tests because it has an IoT base using the NodeMCU ESP32 microcontroller. This tool allows users to not be able to memorize questions like in the color blind test which uses a manual Ishihara book, because the question bank system in this tool involves randomizing the questions and the results can later be accessed via a web server. Keywords: Color Blind, NodeMCU ESP32, Web Server